A summer seduction [large type] - Camp, Candace (Camp, Candace. Legend of St. Dwynwen, 2012)
When someone abducts Damaris Howard from the city streets, Alec Stafford must stake more than his reputation to rescue her. Finding out who's behind a dangerous plot plunges Alec and Damaris together in an intimacy that melts their well-guarded reserve, proving that true love's rich rewards may just be worth the risks.